Sphaeritidae (Coleoptera, Histeroidea) – a new beetle family to the fauna of Kazakhstan - Temreshev, Izbasar I. (Acta Biologica Sibirica, 2024)
False clown beetle Sphaerites glabratus (Fabricius, 1792) is firstly recorded from Kazakhstan. The records of the beetles from family Sphaeritidae were absent for Kazakhstan. The spider Philodromus poecilus (Thorell, 1872) is cited for the first time as a natural enemy of this species.